Pemberdayaan Tokoh Adat dan Tokoh Masyarakat dalam Mencegah Konflik Antar Agama di Kabupaten Aceh Tenggara - Zulfan; Muhammad Hatta (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The 1945 Constitution guarantees and protects religious freedom in Indonesia. There are several laws and regulations as implementing regulations in realizing the ideals of the constitution, such as Law no. 39 of 1999 concerning Human Rights, Law no. 1/PNPS/1965 concerning Prevention of Religious Abuse and/or Blasphemy, and Aceh Qanun No. 4 of 2016 concerning Guidelines for the Maintenance of Religious Harmony and the Establishment of Places of Worship. However, inter-religious conflicts still occur, especially in areas where there are multi-ethnic and religious groups such as Southeast Aceh Regency. Usually, the problem is triggered by a non-tolerant attitude in carrying out social life and carrying out religious rituals and beliefs between religious adherents. In Southeast Aceh district, there are four problems that often trigger disputes or conflicts between religious adherents, namely livestock farming and the sale of pigs in the community, turning on music when the call to prayer is heard, illegal construction of houses of worship, sales of liquor such as "tuak" and construction of houses. gambling freely in the community. This community service program will empower traditional leaders and community leaders through counseling on the importance of preventing conflicts between religious adherents. Traditional leaders and community leaders were chosen because they are closer to all levels of society from various religious backgrounds in Southeast Aceh Regency. The education provided in this activity can be information and increase knowledge for traditional leaders and community leaders in preventing inter-religious conflicts in Kutacane, Southeast Aceh.